EDUKASI PROGRAM LATIHAN OSTEOARTHRITIS KNEE PADA LANSIA DI POSYANDU ORO-ORO DOWO KOTA MALANG - Afifah, Luthfiana Nur; Ika Wardojo, Sri Sunaringsih (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2024)
Osteoarthritis of the knee (OA) is a degenerative joint disease associated with cartilage damage of the joint, where there is a complex interactive degradation process of joints, consisting of repair processes in cartilages, bones, and sinovium followed by secondary components of the inflammatory process. Therefore, the level of understanding about the disease of knee osteoarthritis needs to be increased. An understanding that needs to be at the centre of attention is to know what knee osteoarthritis is, signs and symptoms that can be felt, as well as how to prevent and treat its physiotherapy. The methods used in this examination are physiotherapy education, health promotion and exercise that can be done independently using leaflets to improve elderly knowledge about knee osteoarthritis. The diagnosis work went well and smoothly, resulting in an evaluation of knowledge improvement from 0% to 100%. This activity has improved the understanding of the elderly about the treatment of knee osteoarthritis.